Polycystic Horseshoe Kidney: A Rare Coexistence as a Challenge for the Surgeons. Case Report - Prevezanos, Dionysios; Garmpis, Nikolaos; Dimitroulis, Dimitrios; Garmpi, Anna; Georgakopoulou, Vasiliki Epameinondas; Damaskos, Christos (Acta medica Lituanica, 2022)
Autosomal dominant polycystic kidney disease (ADPKD) with concomitant horseshoe kidney is an extremely rare entity. In this case, we report a 45-year-old male patient with ADPKD and a horseshoe kidney who demonstrated hypertension, urological complications and discomfort symptoms such as pain, breathing difficulties and abdominal meteorism. After preoperative assessment and planning, the patient underwent nephrectomy. Bilateral nephrectomy without dividing the isthmus was performed successfully. The isthmus, which had complicated vasculature and was full of cysts, remained intact avoiding severe bleeding and infection. The postoperative course was uneventful. Keeping the isthmus intact in such cases is a challenge for the surgeon. The rarity of polycystic horseshoe kidney in combination with the altered abdominal anatomy requires the proper preoperative strategy in order to avoid intraoperative complications.
Keywords: polycystic kidney; horseshoe; nephrectomy